Pressure injury in intensive care unit patients during the COVID-19 pandemic (Research, Society and Development, 2022)
Objetivo: Descrever os fatores que favorecem para o desenvolvimento da Lesão Por Pressão e discutir as medidas preventivas pelas unidade de saúde para diminuir o índice de desenvolvimento nas Unidades de Terapia Intensiva durante a pandemia da COVID-19. Methodology: This research is a descriptive, exploratory study, using as technique the Integrative Literature Review. The search was made in the Virtual Health Library (VHL) databases: MEDLINE, BDENF, LILACS and SCIELO, through the junction of three DeCS, crossed with the Boolean operator "AND", as follows: "COVID-19, Pressure Injury, Intensive Care Units". The eligibility criteria were: publications within the Portuguese, English and Spanish languages, between the years 2018 and 2022, that had similarity with the problem question and articles available in full and free form. The ineligibility criteria: simple and expanded abstracts, editorial, theses, dissertations and monographs. Results: Using the three DeCS, 315 articles were found in totality. When adding the criteria the number reduced to 68. After the analysis of the research, 16 publications were selected to compose this research. Discussion: It was identified that prone positioning was the main factor contributing to the emergence of PML, because the patient stays for a long time in the same position. The change of decubitus was presented with more emphasis on control and prevention measures, in addition to prophylactic dressings. Final Considerations: In view of the above, we hope that this study can contribute to improve the quality of life of those involved, enabling new behaviors through the practice of care.